TRANSFER OF RIGHTS TO CULTIVATED LAND ACCORDING TO LAW NO. 18 OF 2021 CONCERNING LAND/AGRARIAN AFFAIRS IN ISLAMIC LEGAL ANALYSIS - Ivan Astavan Manurung; Mhd. Azhali Siregar; Fitri Rafianti (PT. Sinergi Legal Publisher, 2025)
This study examines the transition of rights over cultivated land to private ownership, focusing on Indonesian positive legal regulations and analyzing them from an Islamic legal perspective. The background to this research stems from the reality that much land in Indonesia, particularly ex-HGU (HGU) or abandoned land, has long been cultivated by communities without legal certainty. Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Apartment Units, and Land Registration provides a new legal framework that allows cultivators to obtain ownership rights to the land, provided they meet administrative and substantive requirements. The research method used is normative legal research with a statutory and conceptual approach, examining applicable positive legal provisions and Islamic legal principles related to land ownership and management. Under positive law, the process of transferring rights to cultivated land to ownership involves an inventory of the object and subject, verification of ownership, proof of continuous land management, release of rights from the previous party, and issuance of a certificate by the National Land Agency (BPN). Meanwhile, under Islamic law, land ownership can be obtained through the concepts of ihya' al-mawat (reviving dead land) and iqtha' (land granting by the ruler), with the basic principles of justice (al-'adl), benefit (al-mashlahah), and the prohibition of land abandonment. The analysis shows that the policy in Government Regulation No. 18 of 2021 is in accordance with sharia principles, especially regarding the granting of rights to cultivators who use the land productively and sustainably. The integration of positive law and Islamic law is expected to create a land system that is just, sustainable, and supports the welfare of the community. This study recommends that policy implementation be accompanied by strict supervision to prevent land speculation and ensure that land continues to be used for the common good.